(untitled) - Demetrovics, János (Singapore, 1985)
This book gives an overview of the works performed by the Computer and Automation Institute of the Hungarian Academy of Sciences. Since the late 1970s, there was a need for the recognition of the fundamental role of adequate abstractions and higher level conceptual models in all fields of computer applications. The approach presented explores various conceptual descriptive methods of specification processing.
Keywords: System design,Computer-aided design